Theoretical analysis of telescopic oscillations in multi-walled carbon nanotubes - Zavalniuk, Vladimir; Marchenko, Sergey (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
A simplified theory of the telescopic oscillations in multi-walled carbon nanotubes is developed. The explicit expressions for the telescopic force constants (longitudinal rigidity) and the frequencies of telescopic oscillations are derived. The contribution of small-amplitude telescopic oscillations to the nanotubes low temperature specific heat is estimated.